The estimation methods of occupational skills transferability - Kritkorn Nawakitphaitoon; Russell Ormiston (Journal for Labour Market Research, 2016)
This paper compares two estimation methods of occupational skills transferability, both theoretically and empirically. The first method is based on Shaw's (1984) study, and the second one is based on Ormiston's (2014) study. The main difference between these two methods is that Shaw's skills transferability is a 'market' approach. It is estimated based on an actual occupational change. On the other hand, Ormiston's skills transferability is a 'skills' approach estimated based on the knowledge, skills, and abilities (KSAs) shared across occupations. Although these two approaches produce very different estimates of occupational skills transferability, both estimates significantly explain the earnings losses of displaced workers. In particular, the displaced workers who find jobs in occupations more similar to their previous jobs, as measured by occupational skills transferability, on average, suffer smaller earnings losses than those who find less similar jobs.
Keywords: J31; J62; J63; 330; Schätzung; Dequalifizierung; Kompetenz; Kompetenzstandards; berufliche Qualifikation; Qualifikation; Arbeitsplatzverlust; Einkommenseffekte; Qualifikationsverwertung; Arbeitsplatzwechsel; USA